Automated network profile switcher (ANPROS) / Mohd Zairulhisyam Zakaria - Zakaria, Mohd Zairulhisyam (2007)
Network profile contains the configuration setting of network such as IP addresses on local area network. Usually there will be more than one network profile stored in a notebook of mobile user such as home, office or campus networks. These network profiles apply different setting and configuration. In the campus area, the user will have to apply the campus network profile setting which then enable the users to utilize all network services provided by the network. Dealing with several network profiles make it difficult for the users to manually switch from one profile to another. The users have to reconfigure the IP, subnet mask and default gateway address before they are able to use the network. For average users, these tasks are quite difficult because they have to remember a lots of network information. The Automated Network Profile Switcher (ANProS) solves these problems by providing the user the capability to enable the operating system to automatically switch the network profile without user intervention and restarting the notebook. Therefore it can reduce the time for user to use the network and also provide a more convenient way to handles various network setting for mobile user. The ANProS works by scanning the available network and matched it to suitable existing network profile, thus make it an ideal tool for notebook users. The users only need to manually configure the setting if there is no suitable profile for the network, which means they are in the new local area network. Therefore, the ANProS will offer the mobile user a more comfortable way managing their network setting and providing such as a plug-in-and-play like environment especially to the mobile user.